Solidarność Nauczycielska . pismo pracowników oświaty, no. 48, 1986 - Region Środkowo-Wschodni NSZZ "Solidarność", [auxiliary ed. committee] (NSZZ "Solidarność" Region Środkowo-Wschodni, 1986)
Print run: 500-1000 copies